Blokáda fascia iliaca s celkovou anestezií vs. subarachnoidální blokáda s morfinem u totální náhrady kyčelního kloubu - Kehárová, Kateřina; Pacovský, Vladimír; Nedvěd, Vladimír; Kehárová, Kateřina; Kurzová, Alice; Málek, Jiří (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY Many physicians believe that loco-regional anaesthesia and analgesia improve the postoperative course of patients indicated for total hip arthroplasty compared to general anaesthesia. However, there are many patients who refuse subarachnoid or epidural anaesthesia, or have contraindications or conditions making the use of such techniques impossible. An alternative option is the combination of general anaesthesia and a peripheral nerve blockade. The aim of this prospective randomized open-label clinical trial was to compare the efficacy and quality of postoperative analgesia between fascia iliaca block combined with general anaesthesia (GA) and subarachnoid anaesthesia with morphine and bupivacaine (SAB). MATERIAL AND METHODS After having obtained the ethics committee approval and the patients consent, a prospective, open-label, randomized trial was conducted in patients referred for total hip arthroplasty (THR). The GA group was administered ultrasound-guided fascia iliaca block with 40 ml of 0.25% bupivacaine solution after the induction of general anaesthesia. In the SAB group, subarachnoid blockade was performed with a mixture of 3 ml of 0.5% bupivacaine with 0.150 mg morphine prepared in the hospital pharmacy. Right after surgery the patients were taken to the ICU for 24 hours, after which they were transferred to a general ward. In addition to vital signs monitoring, pain intensity using a 0-10 numeric rating scale (NRS), first morphine administration at NRS >4, total morphine consumption and potential adverse effects were observed over the period of 72 hours. RESULTS There was no statistical difference between the GA (14 persons) and the SAB (14 persons) group in demographic parameters, time to first morphine administration (10 hrs vs. 19 hrs, p=0.10), number of persons with no need for morphine after surgery (5 vs. 7), tingling sensation (1 vs. 0) or numbness of the limb (0 vs. 1). There was no difference in cardiorespiratory parameters or side effects of therapy. In neither case was there respiratory depression or delayed rehabilitation. No patient developed delirium after surgery, and no patient reported dissatisfaction with pain management. DISCUSSION The fascia iliaca block and subarachnoid anaesthesia using local anaesthetic with opioid addition have been repeatedly published for patients after total hip arthroplasty, but this study is unique by comparing the two methods. The study added a new piece of knowledge to the findings of several recent meta-analyses on the comparable outcomes of general and subarachnoid anaesthesia for hip replacement in the perioperative period. CONCLUSIONS If subarachnoid anaesthesia cannot be used in hip arthroplasty, general anaesthesia with fascia iliaca block provides comparable analgesia and quality of postoperative course. Key words: total hip arthroplasty, general anaesthesia, fascia iliaca block, subarachnoid anaesthesia, postoperative analgesia, postoperative course.
Keywords: fascie; celková anestezie; Fascia; nervová blokáda; Arthroplasty, Replacement, Hip; morfin; bupivakain; Morphine; náhrada kyčelního kloubu; Humans; Nerve Block; Pain, Postoperative; Bupivacaine; prospektivní studie; lidé; Anesthesia, General; pooperační bolest; Prospective Studies